Funding Instruction for local authorities in the support of the Afghan Citizens Resettlement Scheme and Afghan Relocation and Assistance Policy : Afghan Relocations and Assistance Policy (ARAP) and Afghan Citizens Resettlement Scheme (ACRS) plus eligible British Nationals : Integration Support : Financial Year 2023-2024.: Afghan Relocations and Assistance Policy (ARAP) and Afghan Citizens Resettlement Scheme (ACRS) plus eligible British Nationals : Integration Support : Financial Year 2023-2024. (2023) - Unknown
No abstract available